Two new species of Xyletinus Latreille (Ptinidae: Xyletininae) in Eocene Baltic amber - Alekseev, Vitalii I.; Bukejs, Andris (Zootaxa, 2019)
New species of the genus Xyletinus Latreille, 1809, namely X. (s.str.) besseli sp. nov. and X. (s.str.) barsevskisi sp. nov., from Eocene Baltic amber, are described and illustrated.